THE MAIN PREREQUISITES FOR THE IMPLEMENTATION OF THE WORKFORCE MANAGEMENT SYSTEM TO OPTIMIZE STAFF WORKING HOURS - V. V. Degtyareva; P. M. Gureev; D. A. Trubkin (Вестник университета, 2021)
The purpose of the article is to study the principles of managing staff working time to reduce costs and increase efficiency, optimize labor processes, manage and predict the workload of staff, and implement methods and tools to improve efficiency. The article describes the main prerequisites for the implementation of the Workforce Management system (WFM), which is a methodology for planning employees’ working hours, which is a component of the personnel management concept. As a metric for evaluating the effect of using WFM systems, the planned or actual number of employees` hours per month is used – a comparison of the planned schedules before and after using the system is made. The effect of implementing WFM is as follows: increased staff efficiency, improved service level, revenue growth as a result of lower costs and more competent traffic coverage, increased staff involvement and saving management time.